PEMERIKSAAN FESES UNTUK IDENTIFIKASI CACING DAN AMOEBA PADA SANTRI DI PONDOK PESANTREN - Luh Titi Handayani (Jurnal SainHealth, 2018)
Islamic boarding school has excesive activity within 24 hours and become a house for living for the students. Crowded environment at islamic boarding school emerging a possibility of communicable disease such as scabies and gastrointestinal disorder. The purpose of this study is to identify the student’s health at islamic boarding school through the infection of amoeba and helminths in their feses. It’s a non experimental reasearch. There were 30 respondents taking part of this research and the sample are taken from instant stool sample. The results show that 46,7% respondents have positive 2 results. It means that there were infection and parasite living in their gastrointestinal tract. The role of clean and healhty behavioral pattern (PHBS) are very important in islamic boarding school environment and it implementation need an integrated role of every part of islamic boarding school such as student, executive organizer and health care worker. The role of kyai and ustadz (teacher) as the role model for the students are needed in order to give the example of implementation of clean and healhty behavioral pattern form health and Islamic perspective